Mobile Simulation Unit: taking simulation to the surgical trainee. Issue 5 (24th February 2014) - Pena, Guilherme; Altree, Meryl; Babidge, Wendy; Field, John; Hewett, Peter; Maddern, Guy
Abstract: Background: Simulation‐based training has become an increasingly accepted part of surgical training. However, simulators are still not widely available to surgical trainees. Some factors that hinder the widespread implementation of simulation‐based training are the lack of standardized methods and equipment, costs and time constraints. We have developed a Mobile Simulation Unit (MSU) that enables trainees to access modern simulation equipment tailored to the needs of the learner at the trainee's workplace. Methods: From July 2012 to December 2012, the MSU visited six hospitals in South Australia, four in metropolitan and two in rural areas. Resident Medical Officers, surgical trainees, Fellows and International Medical Graduates were invited to voluntarily utilize a variety of surgical simulators on offer. Participants were asked to complete a survey about the accessibility of simulation equipment at their workplace, environment of the MSU, equipment available and instruction received. Utilization data were collected. Results: The MSU was available for a total of 303 h over 52 days. Fifty‐five participants were enrolled in the project and each spent on average 118 min utilizing the simulators. The utilization of the total available time was 36%. Participants reported having a poor access to simulation at their workplace and overwhelmingly gave positive feedback regarding their experience in the MSU. Conclusion: The use of the MSU to provide simulation‐based education in surgery is feasible and practical. The MSU provides consistent simulation training at the surgical trainee's workplace, regardless of geographic location, and it has the potential to increase participation in simulation programmes.